“Merapi Volcano Imaginary” an alternative multimedia learning geography in the south region of Merapi volcanism - Muhammad Nursa'ban; Mukminan Mukminan; Mawanti Widyastuti; Dimas Sekar Langit; Muhammad Choirul Anwar (Universitas Negeri Yogyakarta, 2022)
This study aims to anticipate the loss of learning for students in the geography education field practice in the southern region of Merapi Volcano during the Covid-19 Pandemic era by developing Android-based interactive learning multimedia as a medium as well as teaching materials. The development uses the ADDIE method (Analysis, Design, Development, Implementation, and Evaluation). Product feasibility was assessed by six material and media expert lecturers and 10 geography education students as users. The result of the development is an interactive multimedia with flipped book combined with Adobe Flash Maker on Android, with the name